Orderability, contact non-squeezing, and Rabinowitz Floer homology - Albers, Peter; Merry, Will J. (The journal of symplectic geometry, 2018)
We study Liouville fillable contact manifolds $(Σ,ξ)$ with non-zero Rabinowitz Floer homology and assign spectral numbers to paths of contactomorphisms. As a consequence we prove that $\widetilde{Cont_0}(Σ,ξ)$ is orderable in the sense of Eliashberg and Polterovich. This provides a new class of orderable contact manifolds. If the contact manifold is in addition periodic or a prequantization space